Pengembangan Game Edukasi Rhythm Blade Berbasis Virtual Reality Menggunakan Unity dan MDA Framework untuk Inovasi Pembelajaran - Heriadi, Herman (TIN: Terapan Informatika Nusantara, 2025)
Innovation in learning is essential to enhance student engagement and motivation in understanding the material interactively, considering the challenges faced by conventional methods in capturing students' attention. This research aims to develop the Rhythm Blade game based on Virtual Reality (VR) using the Unity Engine as an innovative learning medium. This game is designed by combining elements of music, rhythmic movements, and narrative-based challenges to create an immersive learning experience, aimed at enhancing players' cognitive and motor skills. In its development, this game adopts the Mechanics, Dynamics, Aesthetics (MDA) design approach to balance educational and entertainment aspects. The problem faced is the lack of enjoyable and interactive learning methods in teaching motor and cognitive skills through digital media. The test results show that this game not only succeeded in improving those skills but also provided an enjoyable learning experience. These findings indicate the significant potential of using VR-based games as effective learning aids in the digital era, although improvements are still needed in menu transitions and visual effects to reduce the likelihood of motion sickness in some users. This research makes an important contribution to the application of VR technology in education.